Staphylococcus aureus meticilino resistente en personal de salud de las áreas de neonatología y quemados del Hospital General Isdro Ayora de la ciudad de Loja - Cuenca Riascos, Eulalia Betzabé (2015)
The methicillin-resistant Staphylococcus aureus (MRSA) expresses the determinant mecA gene that confers resistance to penicillin and beta-lactam being a bacterium that causes complicated infections of nosocomial type. The nasal bearer MRSA is the main reservoir and source of infection for individuals with a weakened immune system, if such bearers are healthcare professionals, there would be a risk factor for the patients who are under the care and attention of them. The present descriptive cross-sectional study was performed in the General Hospital Isidro Ayora from the City of Loja, during the period March to August 2015, having as main objective the identification of MRSA in healthcare personnel of the area of neonatology and burned. For the analysis and identification of MRSA there were used conventional bacteriology techniques and standardized guidelines such as 3E protocol of the manual CLSI M100-S24. The sample under study was from 54 individuals which fulfilled the criteria for inclusion. The following outcomes were obtained 31.82% of the health personnel of the area of burned are bearers of Staphylococcus aureus; in the area of neonatology there are a 59.38%. Having a most widely distribution in the masculine sex with a 60%. There were not isolated producers strains of methicillin resistance. Keywords: MRSA (methicillin-resistant Staphylococcus aureus), health personnel, neonatology, burned area